Outcome of interventions to improve the quality of reproductive health services provided by private health facilities in selected states in Nigeria (2006)
In Nigeria, as in many developing countries, the private health sector provides a significant proportion of reproductive health services. However, there are concerns about the quality of the reproductive health services provided by personnel operating in this sector. Few interventions exist to improve the quality of reproductive health services being provided by private practitioners. This three year intervention project, which was implemented in Oyo, Ogun and Gombe States, was designed to improve the capacity of personnel working in the private sector to deliver quality reproductive health service to their clients. One hundred and thirty nine privately owned health facilities participated in the project. Baseline data were collected from staff and clients using these facilities through self-completed questionnaires. A total of 458 nurses/auxiliaries were trained to improve their counseling and service delivery skills; 138 proprietors/proprietresses were trained on total quality management to enhance the quality of reproductive health service; and 84 physicians' knowledge were updated on reproductive health/family planning, and post-abortion care. Provision of contraceptive, drugs for treatment of sexually transmitted infections, supply of equipment and development of educational materials were the other components of the intervention. A follow-up survey was conducted three years after implementing the interventions to gauge outcome. At baseline, only 35.2% managed postpartum sepsis compared to 97.8% at follow-up. Thirty-nine percent provided post-abortion care at baseline the figure rose to 97.2% at follow-up. The proportion of respondents who reportedly provided family planning services increased from 39.5% at baseline to 43.0% at follow-up. Report of managernent of persons living with HIV/AIDS increased from 16.0% to 24.3% while counseling services increased from 36.1 % to 37.6%. At baseline, only 55% of the health workers reported that they had male condoms in stock, the figure rose to 88.2% at follow-up. Sixty-one percent of clients reported that it took 1- 5 minutes before being attended at follow-up, compared to 95% who claimed they spent about an hour before receiving care at baseline. The interventions improved availability and quality of reproductive health services provided by private health facilities. Similar interventions should be replicated to scale up the proportion of private health facilities that provide quality reproductive health services in the country.